Vegetable Consumption Pattern and Health Consciousness of Urban Terrace Garden Farmers - Poornima, C P; Suryawanshi, Pallavi D (Journal of Extension Education, 2020)
A study was conducted to analyse the vegetable consumption pattern and health consciousness of urban households practicing terrace gardening at their homes. The survey was conducted among randomly selected 90 households in Pune city i.e., Pune Municipal Corporation and Pimpri - Chinchwad Municipal Corporation. The study revealed that among the urban wellers doing terrace gardening, everyone showed either moderate or high level of health consciousness and no one showed low level. The amount of vegetables consumed per household per day was taken in to consideration while collecting details regarding general consumption pattern of vegetables. As per the study, it was found that, 70 per cent were consuming moderate amount of vegetables on daily basis.